Development of V-Chata Enteral Formula Based on Mung Bean Flour (Vigna Radiata) and Yellow Pumpkin Flour (Cucurbita Moschata) for Type 2 Diabetes Mellitus Patients - Damayanti, Risya; Moviana, Yenny; Pusparini, Pusparini; Gumilar, Mulus; Purba, Jedya Lucas. A. (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
Nutrition therapy for diabetes mellitus uses enteral nutrition (orally or using a tube) or parenteral nutrition according to the patient's condition. Enteral formulas generally use commercial products that are relatively expensive. The development of V-Chata is expected to be an alternative by using local food ingredients, affordable prices, practical processing, and durability. The study aimed to determine the effect of different formulations of mung bean flour and pumpkin flour on organoleptic properties, flowability, macronutrient, fiber, antioxidant activity, and price. This research design was an experimental that to analyze effect of formulation of mung bean flour and pumpkin flour in formula 1(F1 - 90%:10%), F2 (85%:15%), and F3 (80%:20%) respectively. The result showed that no difference among F1, F2, and F3 for aroma and consistency aspects (p-value> 0.05). But there were difference for color, taste, and overall aspcets (p-value <0.05). Mann-Whitney test results showed that no difference between F1 and F2 for color, taste, and overall aspects. But there was a significant difference between F1 and F3 and F2 and F3. The best enteral formula based on the organoleptic properties test is F1. The flowability of the enteral formula was 4.21 seconds to drain 50 ml in NGT tube 16 Fr. Proximate analys showed energy content 245 kcal, protein 13 g, fat 3 g, carbohydrates 40 g, and fiber 5,48 g per 250 ml serving, meet enteral feeding criteria. Antioxidant activity test results (IC50) showed weak antioxidants. The price per serving is lower 23% than the commersial.